Temperature‐ and pressure‐dependent structural study of {Fe(pmd)2[Ag(CN)2]2}n spin‐crossover compound by neutron Laue diffraction. Issue 3 (1st June 2014) - Rodríguez‐Velamazán, José Alberto; Cañadillas‐Delgado, Laura; Castro, Miguel; McIntyre, Garry J.; Real, José Antonio
<x xml:space="preserve">Abstract</x> The effect of pressure (up to 0.17 GPa) on the spin‐crossover compound {Fe(pmd)2[Ag(CN)2]2}n [orthorhombic isomer (II), pmd = pyrimidine] has been investigated by temperature‐ and pressure‐dependent neutron Laue diffraction and magnetometry. The cooperative high‐spin ↔ low‐spin transition, centred at ca 180 K at ambient pressure, is shifted to higher temperatures as pressure is applied, showing a moderate sensitivity of the compound to pressure, since the spin transition is displaced by ca 140 K GPa−1. The space‐group symmetry (orthorhombic Pccn) remains unchanged over the pressure–temperature (P–T) range studied. The main structural consequence of the high‐spin to low‐spin transition is the contraction of the distorted octahedral [FeN6] chromophores, being more marked in the axial positions (occupied by the pmd units), than in the equatorial positions (occupied by four [Ag(CN)2]− bridging ligands).